Cost of Article Processing Charges to Adhere to National Institutes of Health Public Access Policy - Ryan Huebinger; Marla Hertz; Ryan A. Coute (JAMA Internal Medicine, 2026)
This economic evaluation estimates investigator payments of article processing charges to journal publishers to allow immediate public access to their published federally funded research.